2015
DOI: 10.3892/or.2015.3747
|View full text |Cite
|
Sign up to set email alerts
|

EGR1 regulates radiation-induced apoptosis in head and neck squamous cell carcinoma

Abstract: Abstract. The transcription factor, early growth response 1 (EGR1) belongs to the early growth response family. EGR1 regulates the transactivation of genes involved in growth inhibition and apoptosis by ionizing radiation. The aims of the present study were to evaluate the expression of EGR1, and its relationship to prognosis, in patients with advanced laryngeal and hypopharyngeal squamous cell carcinoma (LHSCC) receiving chemoradiation therapy, and to observe the effect of EGR1 on the apoptosis of head and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…An indication to such complexity as it pertains to EGR1 regulation and its downstream effects is highlighted by the fact that while it is thought to be a tumor suppressor in most malignancies, EGR1 seems to be surprisingly oncogenic in prostate cancer [25, 54, 55]. This observation parallels the evidence suggesting that it can be a positive [2729, 33, 34, 47, 48, 5053] or a negative [25, 28, 30, 41, 5457] regulator of apoptosis in different systems. Instead, we found that EGR1 is neither a positive nor a negative regulator of radiation induced apoptosis in murine bone marrow cells.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…An indication to such complexity as it pertains to EGR1 regulation and its downstream effects is highlighted by the fact that while it is thought to be a tumor suppressor in most malignancies, EGR1 seems to be surprisingly oncogenic in prostate cancer [25, 54, 55]. This observation parallels the evidence suggesting that it can be a positive [2729, 33, 34, 47, 48, 5053] or a negative [25, 28, 30, 41, 5457] regulator of apoptosis in different systems. Instead, we found that EGR1 is neither a positive nor a negative regulator of radiation induced apoptosis in murine bone marrow cells.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have demonstrated that it is a tumor suppressor in several model systems, human malignancies included [29, 45–48]. Haploinsufficiency of EGR1 cooperates with other mutations in the development of murine myeloid neoplasms [19, 26, 49], suggesting it might play a significant role in malignant transformation of stem cells leading to t-MNs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recently published study about the role of ATF3 in colorectal cancer supported the dual role of ATF3 in cancer progression [16]. Similar to ATF3, EGR1 seems to be involved in radiation-induced apoptosis [7,17]. The prior study discussed EGR1 as a biomarker of radiosensitivity in the treatment of HNSCC.…”
Section: Introductionmentioning
confidence: 99%